Penerapan Aplikasi untuk Mengetahui Status Gizi dan Stunting Balita di Posyandu Kantor Kelurahan Birobuli Selatan - Rikwan; Ni Kadek Armini; Ni Ketut Marlina; Sitti Fajrah; Veni Mornalita Kolupe; Arpin; Parmi; Athia Kurnia Kasim; Ummul Khaerah; I Kadek Wartana (LPPM Universitas Widya Nusantara, 2026)
Stunting and toddler nutrition remain public health challenges that require rapid and accurate early detection. This community service activity aims to implement a digital application to determine the nutritional status and detect stunting in toddlers at the Integrated Health Post (Posyandu) at the Birobuli Selatan Village Office. The method used was a participatory approach through the preparation, implementation, and evaluation stages, involving 20 toddler parents, 5 Posyandu cadres, and Birobuli Community Health Center officers. Anthropometric data in the form of age, weight, and height were input into the application to automatically generate nutritional status and stunting diagnoses. The results of the activity showed that the application was able to improve recording efficiency, speed up the analysis process, and support early detection of toddler nutritional status. Of the 20 toddlers examined, 45% had good nutritional status, 15% were undernourished, 20% were severely malnourished, 15% were overnourished, and 5% were obese. Based on the stunting diagnosis, 65% of the toddlers did not experience stunting, 25% had mild stunting, and 10% had severe stunting. The application makes it easier for cadres to manage data and report, thus potentially improving the quality of integrated health post (Posyandu) services and supporting sustainable stunting prevention efforts.